Deteksi Fenomena Chatter Pada Proses Turning Menggunakan Sinyal Suara - Darman Darman; Feblil Huda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Chatter is an excessive vibration that occurs due to performing of tools which have a negative effect that causes poor surface quality, disproportionate use of tools, damage to equipment, and etc. By these reasons chatter has became important research area in mechanical engineering to detect its existence in operational condition of machining process. In this research, the chatter detection method by using sound signal was developed. The artificial chatters were then generated by unsharpening the lathe cutting. The uncalabrated microphone which operated by PC and MATLAB software was then used to grap the sound data from operating turning process. The sound signals in normal and chatter condition were then processed to perform sound signal in the time domain, frequency domain, and spectrogram. The existence of chatters was signed by excessive vibration and bad roughness of turning process product. The Spectogram display TF representation, Time-Magnitude domain and 3D spectrogram. TF representation showing magnitude enhancement, that occurs during the chatter. the Time-Magnitude domain showing time span of the chatter and 3D spectrogram can be seen in the contours and characteristics from chatter. From whole of representation, the chatter can be detected.Keywords : Sound Signal, Chatter, Turning Process, Spectrogram